Analysis of Land Surface Temperature Evolution Based on Regional Road Scope. (12th August 2020) - Liu, Fabao; Jia, Xingli; Li, Wenbin; Du, Ao; Wang, Dang
Abstract : To balance sustainable road construction and environmental impact, intrinsic relationships between regional road networks and land surface temperature (LST) along the roads must be examined. In this study, we hypothesize that expanding road networks can affect the LST within a given region. Thus, we determined the influence of varying road grades on the surrounding LST. Using an improved single-window algorithm with reasonably adjusted water vapor parameters, LST data for the relevant areas were extracted from Landsat 8 data. Analyzing these data revealed that, in the improved single-window algorithm, the MOD05 L2 water vapor parameter could obtain results, indicating that road grades are positively correlated with LST changes when road network mileage is increased. In addition, we found that LST was increased by highways and low-grade roads over distances of 180 m and 150 m compared with the surrounding area, respectively. Furthermore, LST was affected by road interchanges over a distance of 300 m and by intersections formed by low-grade roads over 150 m; both have a linear nonuniform influence on the propagation models. Finally, we determined that different highways in the LST radiation range can interact to form an LST concentration zone, resulting in further LST increases.